Intervention in Students’ Performance in Basic Science and Technology Using Blended Learning Strategies - Gbinde, Felix T.; Achor, Emmanuel E.; Agogo, Peter O. (EDUPEDIA PUBLISHER, 2025)
Purpose: This study investigated the efficacy of two blended learning approaches—Face-to-Face Learning (FFL) and the Online Laboratory Strategy (OLS)—in improving the academic performance of Basic Eight students in Basic Science and Technology in Benue State, Nigeria. Methodology: Employing a quasi-experimental design, the research sampled 210 students from a target population of 27,457 across six secondary schools. Data were collected using the Basic Science and Technology Performance Test (BSTPT), which demonstrated strong internal consistency with a reliability coefficient of 0.88. Findings: Analysis of variance revealed a statistically significant difference in the mean performance scores of students exposed to FFL and OLS compared to those taught using traditional demonstration methods, F(2, 206) = 131.395, p < 0.001. However, no statistically significant gender differences were observed in performance under either FFL (F(1, 71) = 1.685, p = 0.198) or OLS (F(1, 68) = 0.048, p = 0.828), suggesting that the effectiveness of both strategies was independent of gender. These findings underscore the pedagogical value of FFL and OLS in enhancing science learning outcomes. Significance: Consequently, the study recommends that educational policymakers and teacher education institutions adopt and institutionalize these blended learning strategies within curriculum frameworks. Moreover, sustained investment in teacher training and resource provision is essential to maximize the instructional benefits of these approaches and promote equitable, high-quality science education.